Comparison of vapour pressure deficit patterns during cucumber cultivation in a traditional high PE tunnel greenhouse and a tunnel greenhouse equipped with a heat accumulator - Paweł J. Konopacki; Waldemar Treder; Krzysztof Klamkowski (Spanish Journal of Agricultural Research, 2018)
Plant productivity in protected cultivation is highly influenced by air temperature and humidity. The conditions relating to the moisture content of the air in protected plant cultivation are preferably defined by vapour pressure deficit (VPD), which describes the difference between the maximal and actual water vapour pressure (kPa). VPD is widely used as the parameter describing the climate conditions favourable for the development of fungal diseases and for highlighting conditions unfavourable for plant development. In protected cultivation, both the air temperature and the humidity are influenced by heating systems, and one such system is a heat accumulator, which may store the excessive heat produced during the day by converting the solar energy inside the plastic tunnel, and using it when plant heating is required. The tunnel equipped with a heat accumulator maintained an optimal level of humidity for a longer period, and significantly reduced the time of excessive air humidity. The longest time with an optimal VPD was recorded in August in a tunnel with an accumulator – 30.5% of total time vs. 22.3% of time for control tunnel. The highest difference of total time where the VPD was too low (below 0.2 kPa) was recorded in July – 12.4% of time in a tunnel with an accumulator vs. 39.1% of time for control tunnel. The highest difference of total time with an excessive VPD (over 1.4 kPa) was recorded in May – 12.1% of time in a tunnel with an accumulator vs. 17.9% of time for control tunnel. However, a situation beneficial for plant growth occurred every month during the investigated season.